Development of SCaGI website as career information guidance media to improve students' career maturity in senior high school in Boalemo District - Dedi Sukri Tantu; Budi Astuti (University of Muhammadiyah Malang, 2025)
This study aims to develop the SCaGI website as a career information guidance medium to improve the career maturity of senior high school students in Boalemo District, Gorontalo Province. The research was conducted using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. A total of 120 Grade XII students from four high schools were involved, with 18 students identified as having low career maturity. Data collection techniques included interviews, questionnaires, and a career maturity scale. Validation was carried out by material and media experts, and effectiveness testing used a one-group pretest-posttest experimental design. The SCaGI website was evaluated as highly feasible by material experts (97.72%) and media experts (95.45%), and was considered highly practical by guidance and counseling teachers (94.73%). The implementation of the SCaGI website demonstrated significant improvement in students’ career maturity, with an average N-Gain score of 0.76 (76.91%), indicating high effectiveness. These findings suggest that the SCaGI website is a valuable tool for providing accessible and engaging career information, supporting students in making more informed and independent career decisions. This study contributes to digital innovation in guidance and counseling practices and opens opportunities for broader implementation in diverse educational settings.